2018
DOI: 10.5114/ada.2018.77672
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase response and its biomarkers in acute and chronic urticaria

Abstract: IntroductionSince urticaria is a persisting inflammatory disease it is important to establish the prognostic factors for the duration and severity of the disease.AimTo evaluate serum concentrations of selected acute-phase proteins (APP) in patients with various forms of urticaria as compared to healthy volunteers and also to analyze these concentrations in different types of urticaria. Additionally, to evaluate the correlation between serum levels of selected APP and disease activity.Material and methodsSerum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
6
18
2
Order By: Relevance
“…In our study, similar to previous reports, we noted higher IL-6 levels in AU [5] and CU [6] patients. This increase was previously found in patients with antihistamineresistant urticaria [9] and in severe CU compared to patients with mild CU [16]. We did not confirm the correlation of IL-6 levels with disease activity; however, this correlation has been documented in previous work [16][17][18].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In our study, similar to previous reports, we noted higher IL-6 levels in AU [5] and CU [6] patients. This increase was previously found in patients with antihistamineresistant urticaria [9] and in severe CU compared to patients with mild CU [16]. We did not confirm the correlation of IL-6 levels with disease activity; however, this correlation has been documented in previous work [16][17][18].…”
Section: Discussioncontrasting
confidence: 81%
“…At the same time material was collected for laboratory determinations. The activity of urticaria was evaluated according to the TSS (Total Symptom Score) [ 16 ] which is defined as the sum of the scores for the number and size of wheals and severity of pruritus. The maximum diameter of the largest wheal was assessed according to the following scheme: 0 = 0, 1 = diameter ≤ 1.5 cm, 2 = diameter > 1.5 cm and ≤ 2.5 cm, 3 = diameter > 2.5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, bone marrow expression of TfR-1 was decreased following severe trauma, representing the rate-limiting component of iron uptake by erythroid progenitors. 27,35 Loftus et al 27 postulated that for iron homeostasis and normal erythropoiesis, iron bioavailability must be accompanied by iron uptake in erythroid progenitors, which is facilitated by transferrin and its receptor via receptor-mediated endocytosis. Our findings in this study are consistent with the iron homeostasis process following trauma being interrupted both by decreased iron bioavailability due to an increase in hepcidin concentration as well as a decrease in transferrin receptor expression preventing iron uptake by the erythroid progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous studies showed that IL-4 was highly expressed in serum of spontaneous urticaria patients. 19 IL-17 and IL-33 are newly discovered members of the IL-1 family. They can regulate immune responses, positively feedback to Th2 cells, and accelerate the activation of Th2 cells and the release of related cytokines.…”
Section: Discussionmentioning
confidence: 99%